Does tobacco use among adolescents come out of style in Czechia and Slovakia? Findings from the Global Youth Tobacco Survey between 2002 and 2016 - Bašková, Martina; Sovinová, Hana; Csémy, Ladislav; Baška, Tibor; Ochaba, Róbert (Central European Journal of Public Health, 2022)
OBJECTIVES: The aim of this study is to analyse Global Youth Tobacco Survey (GYTS) data on a prevalence of tobacco use, indicators of tobacco control and pro-tobacco activities in Czechia and Slovakia between 2002 and 2016. METHODS: GYTS is a school-based survey of students aged 13-15 years carried out in Czechia and Slovakia in 2002/2003, 2007, 2011 and 2016. Standardized uniform questionnaires provided representative data. RESULTS: Between 2002 and 2016 the current cigarette smoking declined both in Czechia and Slovakia (from 34.6% and 26.4% to 15.2% and 17.1%, respectively). Indicators of tobacco control activities either did not change (access to buy cigarettes by minors) or decreased (school-based and mass media interventions). Indicators of pro-tobacco activities declined (being ever offered by a free tobacco product and having something with a tobacco product brand logo on it). CONCLUSIONS: Tobacco use is on decline and the situation becomes similar to the most of European countries. Preventive activities are only partially responsible for the process. Rather effect of global trends accelerated by widespread use of social media can play a role.
Keywords: Adolescent; Česká republika; Humans; Tobacco Use; tabákové výrobky; prevalence; průzkumy a dotazníky; lidé; Slovenská republika; Nicotiana; Slovakia; Prevalence; tabák; Surveys and Questionnaires; Czech Republic; mladiství; Tobacco Products; užívání tabáku